Velascoa (Crossosomataceae), un género nuevo de la Sierra Madre Oriental de México - Calderon de Rzedowski, Graciela; Rzedowski, Jerzy (Instituto de Ecología, A.C., 1997)
On the basis of specimens collected in the NE extreme of the Mexican state of Querétaro Velascoa recondita is described as a new genus and species. It is considered to be a member of the Crossosomataceae as a rupicolous and microphyllous shrub and because of its flower with a gynoecium of two free carpels, as well as of similarities in the characters of the fruit and of the arillate seed. However, Velascoa differs from the remaining known members of this family in its elongate and tubular hypanthium which bears 10 almost sessile anthers in its distal extreme, as well as in the lack of a nectariferous disk at the base of the pistil.